Eco-Friendly Fish Farming: Responsibly-Sustainable Aquaculture Among ASEAN Countries - Roy C. Borromeo Jr; Jomar M. Urbano; Alice T. Rivera (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2022)
Oceans were regarded as limitless source of fish and surmised that their supply was enough for the growing population. However, the fish sustenance of the seas was transcended by the increasing population's demands. Through the decade, wild fish stocks progressively depleted. Thus, aquaculture has emerged to address capture fisheries insufficiency. This research study aimed to assess aquaculture through its sustainability and effects on the ecosystem of ASEAN countries. This study utilized a Descriptive-Quantitative research design which gathers quantifiable information to describe the object of the study and how it could improve. It also employed data mining techniques. It is determined that Vietnam has the largest aquaculture farm while Indonesia boasts the highest fish production. Most of the ASEAN countries' employment rates in aquaculture-agriculture only amount to less than 15%. The majority of the countries have good aquaculture economies, while some are dependent on the importation of aquaculture products. The five leading ASEAN countries in aquaculture are Indonesia, Vietnam, Thailand, Philippines, and Myanmar, respectively. Aquaculture reduces fishing pressure on wild stocks but uses lots of shared resources that may hinder environment. “Responsible Aquaculture Standards in Vietnam